Respuesta :
Answer:
The solution is x = -2, y = 4.
Step-by-step explanation:
2x + 4y = 12
x + y = 2
From the second equation: y = 2 - x.
Now substitute for y in the first equation:
2x + 4(2 - x) = 12
2x + 8 - 4x = 12
-2x = 4
x = -2.
Now find y by substituting x = -2 in the second equation:
- 2 + y = 2
y = 4.
Answer:
x = -2, y = 4
Step-by-step explanation:
Minus y from both sides of x+y=2
x=−y+2
substitute x in 2(−y+2)+4y=12
2y+4+−4=12+−4
2y=8
divide 2 from both sides
y = 4
substitute y in x+-4+2
x = -4 + 2
x = -2